A Comparative Study of Basic Science Process Skills of Science Students at Higher Secondary Level in District Rawalpindi, Pakistan - M. Ahmed; F. R. Choudhary; S. Sultan (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Science process skills (SPS) had a pivotal role in scientific investigation. SPS are very important to be developed in science learning because with the help of SPS students develop their thoughts to make discoveries using scientific investigation. In the 21st century SPS are needed in science learning. In Pakistan results of many studies showed that private sector institutes’ students were performing better than the public sector institutes’ students in the subject of science. Better performance in science is only possible when students have a high level of science process skills. The main purpose of this study was to determine students’ level of performance on basic science process skill and to compare the performance of public and private school Physics students in science process skills at the H.S.S.C. level. A Simple comparative research design was used to compare the skill level of students. In the present study four aspects, of basic science process skills (Observation, Communication, Measurement, and Relationship) were observed. Through purposive sampling technique two top-level colleges, one from the public school system and one from the private school system of the city of Rawalpindi, were selected for the study. For data collection researcher used an observation sheet and worksheet based on four experiments of physics at higher secondary school certificate level. Measurement of SPS was done when students were performing experiments in practical labs. t-test was employed to compare the performance of public and private school students. The result of the research stated that there was a significant difference in basic science process skills of public and private school physics students at the H.S.S.C level. The mean score of performance of public and private school students was observed to be good in the aspects of observation and relationship skills but still teachers need to improve the performance of students in the aspects of communication and measurement skills. Further it is recommended that exam system may give more weightage to science process skills so that students and teacher of science subjects may be able to concentrate more on this aspect of learning.